Hungarian Monitoring, 23 June 1990 . [Magyar rádiófigyelő], 1990. június 23 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Ivan Polozkov the general secretary of the Russian CP - The Soviet Union may receive West German aid - Talks to form a government in Czechoslovakia - Solidarity plans protest movements Domestic Affairs: - France lifts visa restriction on Hungary - Press festival and the Budapest International Fair - Parliamentary election fraud - Fire rages in Miskolc Economy: - Distributing broadcasting frequencies - Arzenal Ltd. and the arms trade - FRG would extend credit to Hungary - Economic agreements with the GDR in danger Külpolitika: - Ivan Poloszkov az oroszországi KP első titkára - NSZK-segélyt kaphat a Szovjetunió - kormányalakítási tárgyalások Csehszlovákiában - tiltakozó megmozdulásokat szervez a Szolidaritás Belpolitika: - Franciaország megszünteti a vízumkényszert Magyarországgal szemben - sajtófesztivál és BNV - csalások az országgyűlési szavazásokon - tűz pusztított Miskolcon Gazdaság: - a hullámsávok elosztása - Arzenal Kft. és fegyverkereskedelem - az NSZK hitelezne Magyarországnak - veszélyben az NDK-val kötött gazdasági szerződések